Early Laparoscopic Versus Open Cholecystectomy for Acute Cholecystitis - Mumtaz K. H. AL-Nasir (مجله كليه طب الكندي, 2007)
Background: Acute cholecystitis is common surgical problem, which was treated previously by conservative treatment .Later early open has been introduced as an alternative to interval for treatment of acute cholecystitis. Early open was found to be a safe, successful with comparable postoperative complication rate. With the advent of laparoscopy laparoscopic have been used for chronic cholecystitis and became the first line of treatment. New reports have shown that laparoscopic can be used as an alternative to open for surgical treatment of acute cholecystitis. Objectives: to compare the success, safety of early laparoscopic versus early open as a primary treatment of acute cholecystitis. Methods: out of 68 patients were treated for clinical acute cholecystitis between January 2002 and February 2004 in the department of surgery, at Al – Kindy teaching hospital. A total of 62 patients underwent early for acute cholecystitis as soon as possible after diagnosis. The preferred preoperative imaging technique was ultrasound. 30 (48.3%) of the operations were attempted laparoscopically, whereas the remaining 32 patients (51.7%) underwent initial open . Results: The mean operative time for the open cases was 75 minutes versus 60 minutes for the laparoscopic group. There was no perioperative mortality in either group. The incidence of conversion to open was 10% (3 patients). Surgical complications related to laparoscopic and open occurred in 2 (6.6%) and 3 (9.3%) cases, respectively. There was no difference between the open and laparoscopic groups in regard to the major postoperative complications. Conclusion: The current study shows that early (whether performed by open or laparoscopically) is a safe and effective treatment for acute cholecystitis. Low conversion rates can be maintained with strict guidelines for appropriate patient selection, adequate experience, and proper laparoscopic technique.